Study on the exhibition performance and efficiency of exhibitors in overseas trade show: Company characteristics and exhibition participation - Hee Yeon Lee; Chang Won Park; Bong-Seok Kim (Global Business & Finance Review (GBFR), 2021)
Purpose: This study aims to analyze the efficiency of performance of exhibitors in overseas trade shows and identify the causes of inefficiency and differences according to their characteristics. Design/methodology/approach: This study employed a theoretical approach based on a literature research and an empirical analysis of companies that benefited from overseas exhibition support policies. Data envelopment analysis was used as a research method for analyzing the efficiency of 221 participating companies in overseas trade shows. Findings: The result exhibited little difference in the overall efficiency of exhibition performance according to the characteristics of exhibitors. However, performance in terms of the development of overseas markets differed dependent on the sales and export volume of exhibitors and the region of the trade shows. Furthermore, the finding demonstrated that net sales, exports, items, frequency of exhibiting in a trade show, and the rate of self-expenditure of the total costs of trade shows influence export promotion performance. Research limitations/implications: This study is significant in that it measured the efficiency of exhibition performance compared with the input of exhibitors in trade shows. However, the input variable was fixed and efficiency was analyzed using only a combination of three output variables. Thus, employing various input and output variables determine the causes of efficiency and inefficiency will lead to meaningful studies. Originality/value: This study measured the effectiveness of the overseas exhibition support policies of the government and the differences in the efficiency of exhibition performance according to the characteristics of beneficiary companies. This study differed from previous studies that simply analyzed the exhibition performance of companies. The results can be used as basic data necessary for establishing support policies for decision makers through measures for improvement, such as standards, contents, methods, and methods, as well as measures for the maximization of the efficiency of exhibition performance according to the characteristics of exhibitors
Keywords: 650; Exhibitor; Overseas exhibition; Exhibition performance; Exhibition; Trade Show; Efficiency; Data envelopment analysis